Aspect ratio control and sensing applications for a slot waveguide with a multimode stub. (23rd June 2016) - He, Zhihui; Peng, Yongyi; Li, Boxun; Chen, Zhiquan; Xu, Hui; Zheng, Mingfei; Li, Hongjian
Abstract: We report the aspect ratio control and sensing applications for metal–dielectric–metal (MDM) slot waveguides with a multimode stub. By adjusting the aspect ratio r = h / w of the stub, five types of optical evolutions in various aspect ratio r ranges are defined. We can realize a single or double plasmon-induced transparency (PIT) as well as Fano resonances. In addition, the figure of merit (FOM), which can describe the sensing performance of structures, is discussed in our paper. We can find up to three FOM peaks in our proposed structure. These findings provide guidance for the fundamental research of integrated plasmonic sensors.